Preparation of Security Professionals or from Security Education to National Security Studies - Eugeniusz NOWAK (Communications of International Proceedings, 2020)
Objective: To propose solutions ensuring continuity and effectiveness of teaching security at all stages of education, in order to properly prepare security professionals. Security is becoming increasingly desirable asset, both from the individual and collective standpoint. Ensuring security is a fundamental duty of the state, which is by its very nature called upon to ensure national security. These expectations are met by the National Security Studies, preparing staff of bodies and organisations dealing with ensuring security in the case of threats of non-military nature. Despite this, even the best curriculum can fall victim to the so-called isolationism or siloisation of individual study topics, which leads to a number of unfavourable phenomena, including underestimation of didactic unitarianism, lack of educational content correlation between various subjects, redundant educational content, difficulties in implementing innovations, and many more. These problems with study curricula can and should be eliminated. The presented paper offers a number of proposal in this regard. A professional is defined as a person who possesses great skills in a given job and who does their job as well as they can. Therefore, the process of National Security studies should be determined by shaping the professional skills of the graduates. Methodology The solutions proposed in the article are based on the results of studies presented by subject literature [1, 2]. Theoretical methods (analysis, synthesis and analogy) and empirical methods were used in the study process. Empirical methods were dominated by the survey method, mostly focusing on the interview technique. Article type: academic paper.
Keywords: Security; State Security; Safety Education; National Security Studies.